2017
DOI: 10.3389/fphar.2017.00699
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Genistein and Daidzein on Estrogen Conjugations in Human Breast Cancer Cells: A Targeted Metabolomics Approach

Abstract: The beneficial effect of dietary soy food intake, especially for women diagnosed with breast cancer, is controversial, as in vitro data has shown that the soy isoflavones genistein and daidzein may even stimulate the proliferation of estrogen-receptor alpha positive (ERα+) breast cancer cells at low concentrations. As genistein and daidzein are known to inhibit key enzymes in the steroid metabolism pathway, and thus may influence levels of active estrogens, we investigated the impacts of genistein and daidzein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 32 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…These results may explain the anticancer activity of isoflavones. Although this is an area that requires further research, it is believed that there is no harm in breast cancer patients taking isoflavones other than their suppressive effect on tamoxifen, a breast cancer-treating drug [185][186][187][188][189][190][191][192][193][194][195][196]. Studies have shown that despite reducing the action of tamoxifen [197], isoflavones decrease mortality and recurrence rates as well as metastasis in breast cancer patients [198,199].…”
Section: Anticarcinogenic Activity Through Gene Regulationmentioning
confidence: 99%
“…These results may explain the anticancer activity of isoflavones. Although this is an area that requires further research, it is believed that there is no harm in breast cancer patients taking isoflavones other than their suppressive effect on tamoxifen, a breast cancer-treating drug [185][186][187][188][189][190][191][192][193][194][195][196]. Studies have shown that despite reducing the action of tamoxifen [197], isoflavones decrease mortality and recurrence rates as well as metastasis in breast cancer patients [198,199].…”
Section: Anticarcinogenic Activity Through Gene Regulationmentioning
confidence: 99%
“…Furthermore, phytoestrogens may inhibit estrogen metabolic enzymes. Genistein impacts the formation of estrogen metabolites and is a potent inhibitor of E1 and E2 sulfation (Poschner et al, 2017 ). Cytochrome P450 CYP1 family enzymes such as CYP1A1, CYP1A2, and CYP1B1 are important enzymes in estrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although some in vitro and in vivo studies point to the benefits of phytoestrogens, data available from studies with human subjects are inconclusive as to whether consumption of phytoestrogens is entirely beneficial (Cederroth & Nef, 2009;Poschner et al, 2017;Xiao, Zhang, Tong, & Shi, 2017). Studies have even pointed out that genistein interferes with the inhibitory effects of tamoxifen on breast cancer cell growth Spagnuolo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%